(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper presents a multistep approach for segmenting and compressing satellite based land images acquired from Google Maps in accordance to reduce the storage space and transmission time requirements. Land images are often noisy thus first step involves removing noise by using Adaptive Filter for better enhancement of the image. Then Region Based Segmentation is performed to achieve the uniform regions of an image that helps in mapping areas. Finally compression is performed. This work proposed Fractal Lossy Compression algorithm for compressing Land images as it has tendency to produce efficient and optimal results in different applications. The performance of proposed algorithm is compared with other lossy compression technique i.e Cartesian Perceptual Compression based on some parameters. Experimental results proved that the proposed technique is more efficient, effective and accurate as compared to Cartesian Perceptual Compression